Analysis of Determinants of Economic Growth in Central Kalimantan Province - Faisal Asrawi; Andrie Elia Embang; Miar Bakar (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
ABSTRACT This study aims to determine and analyze the effect of capital expenditure on economic growth in Central Kalimantan Province, to find out and analyze the effect of investment in the form of domestic investment (PMDN) on economic growth in Central Kalimantan Province, to find out and analyze the effect of investment in foreign investment (PMA) on economic growth in Central Kalimantan Province, to find out and analyze the influence of exports on economic growth in Central Kalimantan Province. The research method used is descriptive quantitative with time series secondary data 1995-2014. Then the data will be analyzed using multiple linear analysis. The results showed that capital expenditure has a positive and significant effect on economic growth in Central Kalimantan Province, domestic investment (PMDN) has a positive and significant effect on economic growth in Central Kalimantan Province, foreign investment (PMA) has a negative and not significant effect on growth economy in Central Kalimantan Province, exports have a negative and not significant effect on economic growth in Central Kalimantan Province.